Influência do teor de calcário no comportamento físico, mecânico e microestrutural de cerâmicas estruturais - Soares, Roberto Arruda Lima (2008)
There are ores of clay in Piauí State that are used for red structural ceramics, which are naturally contaminated with calcareous vein. This is one thing that impedes its exploration in an adequate way, especially for tile production. The present work aims at verifying the influence of the calcareous contents in the technological structural ceramics area, seeking to determine a maximum permissible calcareous proportion/contents in the ceramic mass using the patterns of the local industry production. For the consecution of this paper, it was characterized the clay and calcareous material by FRX, DRX, TGA and DTA. It was also configurated by extrusion and burnt in the temperatures of 850°C, 900°C, 950°C and 1000°C pieces of the corpus with 0, 5, 10, 15 e 20% of calcareous proportion. After that, it was carried out technological samples of linear retraction, water absortion, apparent porosity, specific apparent mass and mechanic resistance. The results showed the possibility of using calcareous in the ceramic mass and in some cases the technological properties got better